The narrow limits of Ethiopia's national dialogue: In its current form, the process will do little to address the country's structural problems - Gerrit Kurtz (Stiftung Wissenschaft und Politik (SWP), 2024)
Ethiopia has long been in a period of upheaval characterised by massive levels of violence. Relations between the largest ethnic groups are in flux, as is their relationship with the government. The state lacks legitimacy in the central regions of the country, its monopoly on the use of force is contested, and it does not have enough financial resources to provide for the population on a nationwide scale. The national dialogue is intended to facilitate Ethiopia's transformation and increase support for the state among the population. However, the conditions for a confidence-building dialogue are not in place, given the armed uprisings in the two most populous states of Amhara and Oromia; the severely restricted independence of the media and freedom of expression; and the dominance of the ruling party in parliament and society. An additional structured dialogue at the level of the most important political players could mitigate one of the main weaknesses of the process. International actors who, like Germany, support the national dialogue should be careful not to allow themselves to be used for authoritarian consolidation.
Keywords: 320; peacebuilding; transitional justice; Ethiopian National Dialogue Commission; ENDC; Abiy Ahmed; Amhara; Tigray; Oromia; Oromo; Tigray People's Liberation Front; TPLF; Fano rebels; Multi-stakeholder Initiative for National Dialogue; Prosperity Party; Joint Council of Political Parties; Oromo Liberation Front; Oromo Federalist Congress; Oromo Liberation Army; OLA; Ethiopia Peace Observatory